2017
DOI: 10.1002/syn.21965
|View full text |Cite
|
Sign up to set email alerts
|

Spread of tau down neural circuits precedes synapse and neuronal loss in the rTgTauEC mouse model of early Alzheimer's disease

Abstract: Synaptic dysfunction and loss is the strongest pathological correlate of cognitive decline in Alzheimer's disease (AD) with increasing evidence implicating neuropathological tau protein in this process. Despite the knowledge that tau spreads through defined synaptic circuits, it is currently unknown whether synapse loss occurs before the accumulation of tau or as a consequence. To address this, we have used array tomography to examine an rTgTauEC mouse model expressing a P301L human tau transgene and a transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 38 publications
3
47
0
Order By: Relevance
“…Instead, they initiate a selective axonal transport dysfunction that precedes synaptic loss, and in isolation does not result in axonal degeneration or cell death. Furthermore, we provide the first direct evidence for the suggestion that disintegration or death of neurons containing tau seeds does not need to occur in order to propagate tau pathology 20 , and show that tau propagation precedes synaptic or neuronal degeneration. This is in agreement with a recent study showing that spread of tau seeds precedes tangle pathology in the human brain 21 .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Instead, they initiate a selective axonal transport dysfunction that precedes synaptic loss, and in isolation does not result in axonal degeneration or cell death. Furthermore, we provide the first direct evidence for the suggestion that disintegration or death of neurons containing tau seeds does not need to occur in order to propagate tau pathology 20 , and show that tau propagation precedes synaptic or neuronal degeneration. This is in agreement with a recent study showing that spread of tau seeds precedes tangle pathology in the human brain 21 .…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, it has been suggested that one mechanism for the propagation of tau pathology is release following the disintegration and death of the tangle-bearing neurons 19 . In contrast, recent studies have shown that intact neurons exist in areas of pathology propagation in mouse models 20 , and have detected tau species capable of seeding misfolding in brain areas free of tangle pathology in human brains 21 . This suggests potential release of pathogenic tau from living neurons.…”
mentioning
confidence: 95%
“…Array Tomography-The array tomography protocol was applied using previously described methods (17,18). Briefly, a 1 cm 3 section was taken from the superior frontal cortex was fixed, dehydrated and polymerized in 100% LR-white resin.…”
Section: Methodsmentioning
confidence: 99%
“…Postmortem analysis in AD patients has shown the presence and symmetrical distribution of misfolded tau over pre‐ and postsynapses . Recent findings demonstrate the ability of human P301L tau to spread trans‐synaptically before the degeneration of axonal terminals rather than through leakage . Furthermore, Yoshiyama et al.…”
Section: Synaptically Connected Spreading Of Aggregatesmentioning
confidence: 97%